Sustainability of shared economy in the agri-food, tourism, and hospitality industries - Alloh, Karel; Abrham, Josef; Sanova, Petra; Čermák, Michal; Petrzilka, Slavibor; Schilla, Filip (Frontiers in Sustainable Food Systems, 2024)
Introduction: This study aims to provide a systematic literature review on the sustainability of shared economy in the food, agricultural, and hospitality sectors. We assess relationships between the sharing economy and sustainability in the examined industries. Furthermore, we identify gaps in knowledge and recommend possible research directions for future studies. Methods: This study provides a systematic literature review on sustainable sharing economy in the hospitality and agri-food sectors. We applied the Procedure for Systematic Reviews and Meta-Analyses (PRISMA). Based on the mentioned methodological procedure, we conducted a literature search through scientific databases Scopus and Web of Science. The research period is 2014-2023. Results: Using the Procedure for Systematic Reviews and Meta-Analyses (PRISMA), we extracted 2185 scientific articles from the Scopus and Web of Science databases published between 2014 and 2023. A total of 117 studies met the eligibility criteria. Based on the review, we identified the following frequently researched areas in the literature: sustainable housing sharing, urban and community sustainability, energy efficiency and carbon footprint, public sector regulation and sustainability, food sharing, exchanges and networks, food waste-reducing platforms, and food-based applications.The studies reviewed confirmed growing research interest in the sustainability of the shared economy in agri-food and hospitality. The number of studies in the Web of Science and Scopus databases has increased over the last decade. Our systematic review indicates that shared accommodation and food sharing are dominant topics in the literature. The sustainability of shared accommodation has been examined in previous studies, mainly concerning the impacts on cities and communities. In food sharing, we identified relevant linkages between food waste and sharing platforms.